Tindakan Agronomi dan Produktivitas Kebun Kakao Rakyat di Desa Betung, Kecamatan Kumpeh Ilir, Kabupaten Muaro Jambi - Nengsih, Yulistiati; Nasamsir, Nasamsir; Adistya, Adilla; Andriyani, Lizyanti; Daulay, Muhammad Ferdinan Iko (Jurnal Media Pertanian, 2025)
Low cocoa productivity, especially in smallholder plantations, is caused by soil conditions showing symptoms of "soil fatigue", increasing old plants, attacks by cocoa fruit borers (PBK), and vascular wilt (VSD), and fertilization that is not in accordance with the dose. This study aims to determine the intensity of attacks by cocoa fruit-sucking ladybugs (Helopeltis sp.) on smallholder plantations in Betung Village, Kumpeh Ilir District, Muaro Jambi Regency. This research was conducted from March to August 2024 on smallholder plantations in Betung Village, Kumpeh Ilir District, Muaro Jambi Regency. The method used in this study is the survey method. The procedure for determining the location of the study was carried out by purposive sampling. A total of 2 plantation locations became research areas with a land area of 1 ha each. The distance between the two locations is ± 1 meter. The observation method is carried out by transect or surrounding the garden according to the predetermined direction of the track. The number of plant populations at locations 1 and 2 was 600 stems (>100) so 15% of the sample plants were taken so that the number of sample plants taken was 15% of the 600 plants = 90 plants. The variables observed in this study were the type of clone and age of the plant, the number of shade plants and light intensity, the number of main branches of the cocoa plant, agronomic measures, temperature and humidity, production estimates, the level of ladybug pest attacks, the intensity of ladybug pest attacks on each plant. The results showed that cocoa plants were cultivated with a polyclonal system using MCC 02, S1 and S2 clones. The age of the plants varied with a range of 7 to 15 years. The permanent shade used in cultivation was the duku plant with a planting distance of 10 x 10 m. Standard agronomic actions have been carried out on plantation 1 and plantation 2, only the maintenance intensity is much better on plantation 1. The intensity of cocoa fruit sucking ladybug pest attacks on the people's plantation in Betung Village, Kumpeh Ilir District, Muaro Jambi Regency in plantation 2 was 53.08% and on plantation 1 was 22.38%. The level of fruit sucking ladybug pest attacks on the people's plantation in Betung Village, Kumpeh Ilir District, Muaro Jambi Regency in plantation 2 was 63.37% on plantation 1 was 35.18% 1. The level of attack and intensity of fruit sucking ladybug pest attacks in this study were included in the moderate category for plantation 1 and severe for plantation 2. Agronomic actions, level of attack, intensity of fruit sucking ladybug pest attacks caused differences in production, plantation 1 was 842.4 kg/ha/year and in plantation 2 was 576 kg/ha/year